Akuntansi Keuangan Masjid dalam Meningkatkan Kesejahteraan Jama’ah di Masjid Al-Yaqin Kabupaten Sukabumi - Triutami, Annisa Dwi; Machendrawaty, Nanih; Aripudin, Acep (Tadbir: Jurnal Manajemen Dakwah, 2024)
Mosque Financial Accounting ideally uses accounting standards for use in statements of financial position at the end of the period, statements of profit and loss and other comprehensive income during the period, reports of changes in equity during the period, statements of cash flows, notes to financial statement. The purpose of this writing is to find out the general description of mosque management at Al-Yaqin Mosque, and to find out the implications of this management for professional mosque financial management. The purpose of this research is to find out the Management of Al-Yaqin Mosque. Based on data techniques processed descriptive research method with a qualitative approach. The results of this study reveal that the management of the mosque has been managed quite well with the sources of funds obtained by the Al-Yaqin Sukabumi mosque coming from infaq, alms, charity boxes, rice sales collected by the congregation and donors, so that the welfare of the congregation can be created. The financial management of the Al-Yaqin Mosque is presented very simply and refers to the financial reports of the mosque in general. Al-Yaqin Mosque has not implemented a financial management system according to Statement of Accounting Standards No. 1 (PSAK 1).